2020
DOI: 10.1080/10749357.2020.1845014
|View full text |Cite
|
Sign up to set email alerts
|

Interventions used by allied health professionals in sexual rehabilitation after stroke: A systematic review

Abstract: Word count: 249 Background: Although sexuality can be affected post-stroke, few individuals receive sexual rehabilitation because of clinicians' lack of knowledge regarding evidence-based interventions. Objective: To document and describe the best available evidence supporting interventions that target post-stroke rehabilitation of sexuality. Methods: This systematic review searched the databases Medline, Embase, Psycinfo, CINAHL, Web of science, PEDRO and OTSeeker up to May 29, 2020. Inclusion criteria were: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…These categories would aid implementation teams in comprehending what elements, or determinants, are most or least likely to influence practices or behaviors. Indeed, their systematic review showed that only multidisciplinary and structured interventions, including sexual counselling and pelvic-floor-muscle training, may be supported to improve sexual function in the rehabilitation setting [ 56 ]. Moreover, in a recent extensive review, the same authors aimed at identifying the assessment methods used by rehabilitation professionals to investigate sexuality in post-stroke patients [ 57 ], before any rehabilitative approach is applied.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…These categories would aid implementation teams in comprehending what elements, or determinants, are most or least likely to influence practices or behaviors. Indeed, their systematic review showed that only multidisciplinary and structured interventions, including sexual counselling and pelvic-floor-muscle training, may be supported to improve sexual function in the rehabilitation setting [ 56 ]. Moreover, in a recent extensive review, the same authors aimed at identifying the assessment methods used by rehabilitation professionals to investigate sexuality in post-stroke patients [ 57 ], before any rehabilitative approach is applied.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…In addition, the influence of psycho-emotional and social aspects-depression, anxiety, fear, changes in self-perception, and changes in the couple's role-has a direct impact on sexual quality in women post-stroke. Post-stroke rehabilitation focused on SD traditionally targets psychological characteristics, disregarding anatomical and physical aspects that can interfere with sexual function [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It is thus imperative that patients are provided evidence-based sexuality rehabilitation. A recent systematic review [ 21 ] found benefits of carrying out sexual rehabilitation using an interdisciplinary approach for people who sustained a stroke, which included specific skills development [ 22 ], pelvic floor muscle training [ 23 ] and education [ 24 , 25 ]. Moreover, this review suggested a need for more robust studies in the field of sexual rehabilitation, considering that only four randomized controlled trials were found in the literature [ 21 ].…”
Section: Introductionmentioning
confidence: 99%